2018
DOI: 10.1155/2018/2917981
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Protective Role of Brain CYP2J in Parkinson’s Disease Models

Abstract: CYP2J proteins are present in the neural cells of human and rodent brain regions. The aim of this study was to investigate the role of brain CYP2J in Parkinson's disease. Rats received right unilateral injection with lipopolysaccharide (LPS) or 6-hydroxydopamine (6-OHDA) in the substantia nigra following transfection with or without the CYP2J3 expression vector. Compared with LPS-treated rats, CYP2J3 transfection significantly decreased apomorphine-induced rotation by 57.3% at day 12 and 47.0% at day 21 after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide, affecting up to 1% of the global aged population over 60 years [1]. It is mainly characterized by a progressive degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc) [2], which leads to striatal dopamine deficiency and results in motor symptoms such as postural instability, uncontrollable tremor, rigidity, and bradykinesia [3, 4]. Apart from motor symptoms, nonmotor symptoms, including autonomic dysfunction, sleep disturbances, cognitive problems, and depression, are commonly observed in PD [5].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide, affecting up to 1% of the global aged population over 60 years [1]. It is mainly characterized by a progressive degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc) [2], which leads to striatal dopamine deficiency and results in motor symptoms such as postural instability, uncontrollable tremor, rigidity, and bradykinesia [3, 4]. Apart from motor symptoms, nonmotor symptoms, including autonomic dysfunction, sleep disturbances, cognitive problems, and depression, are commonly observed in PD [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that berberine has therapeutic potential against various neurodegenerative diseases, including Parkinson's, Alzheimer's, and Huntington's diseases [6]. Our previous studies have shown that CYP2J2 expressed in the brain plays a protective role in Parkinson's disease models [21]. We can, thus, speculate that one of the possible mechanisms of the therapeutic effects of berberine in neurodegenerative diseases may be the regulation of CYP2J2 expression in the brain through an increase in PPARα/RXRα heterodimer formation and binding to the CYP2J2 promoter.…”
Section: Discussionmentioning
confidence: 98%
“…CYP2J2 encodes a 502 amino acid protein that is primarily expressed in the heart, and, to a lesser degree, in the brain, pancreas, liver, kidney, gastrointestinal tract, and skeletal muscle [14]. Our previous data have shown that CYP2J2 expressed in the brain plays a protective role in Parkinson's disease models [21]. The neuroprotective effect of berberine in neurodegenerative diseases may be CYP2J2-dependent, possibly involving the catalysis of EET production from AA.…”
Section: Introductionmentioning
confidence: 99%
“…LPS (from Escherichia coli , serotype O55:B5, Sigma-Aldrich, St. Louis, MO, USA) dissolved in phosphate-buffered saline (PBS) was injected (10 μ g, 2 μ l) into the SNpc of the rats at a rate of 0.2 μ l/min by an automatic injector (CMA 402, CMA Microdialysis AB, Sweden) [ 18 , 19 ]. The syringe was left in situ for 5 min.…”
Section: Methodsmentioning
confidence: 99%